Implementasi Tata Kelola Dana Desa dalam Pembangunan dan Pemberdayaan Masyarakat Desa - Mia Eka Wahyuni; Herry Yulistiyono (Jurnal Ilmiah Aset, 2021)
This study aims to implement the implementation of village financial management and the implementation of the principles of good governance. With the increasing number of Village Funds accompanied by good village government governance in managing Village Funds by looking at 9 principles, namely the principle of rule of law, the principle of participation, the principle of transparency, the principle of responsiveness, the principle of consensus, the principle of effectiveness and efficiency, the principle of justice, the principle of accountability, strategic vision principle. This type of research is a qualitative descriptive research using normative juridical research methods. Research data collection techniques using literature studies and field studies. Based on theresults of this study and in accordance with the Legislation document and the answers given by the respondents to the researcher, that there is a discrepancy between Government Regulation Number 60 of 2014 and Regent's Regulation Number 2 of 2020 regarding the amount of Village Funds given to each village, in addition to that the level of community participation in the supervision of village fund management. However, in planning, the community is actively involved in village Musrenbang activities, and community participation is also seen in the implementation of village development.